Castleman Disease of Adrenal Masquerades as Adrenal Carcinoma; Review Article on Current Treatment Modalities - Nik Amin Sahid Nik Lah; Firdaus Hayati; Challa Venkata Rao; Nornazirah Azizan; AK Khasnizal (2020)
Castleman disease is a rare lymphoproliferative disorder. Only few cases reported worldwide since first describe in 1956. Only 2 percent of CD involve pararenal location. We report on a 16 years old lady with solitary Castleman disease of hyaline vascular type, involving right adrenal. Patient underwent right open adrenalectomy and no evidence of disease recurrence in 1 year follow up after surgery. In addition, we also discuss on the pathogenesis of the disease, clinical features and option of treatment.